Critical Congenital Heart Diseases as Life-threatening Conditions in the Emergency Room - Togănel Rodica (Journal of Cardiovascular Emergencies, 2016)
Critical congenital heart disease (CHD) represents a special type of cardiovascular emergency due to the complexity of the associated pathology. In many cases, urgent surgery or catheter-based intervention is required as the condition might be life-threatening. In patients with ductal-dependent lesions, closure of the patent ductus arteriosus (PDA) within the first few days postpartum, can cause sudden clinical deterioration with potentially life-threatening consequences. The diagnostic challenges, clinical presentation and particularities related to the closure of PDA in life-threatening critical CHD are presented.